Legal Protection and Legal Certainty Given by the State to Internship Participants in Employment Relations - Edi Sarwono; Azis Budianto (Journal Of Social Science (JoSS), 2025)
This study discusses the legal protection and legal certainty provided by the state to internship participants in employment relations in Indonesia. Although internships aim to improve the competence of prospective workers, their practices are misused by companies as a form of disguised employment relations without fulfilling the normative rights of participants. Through a normative legal approach and analysis of applicable laws and regulations, this study highlights the significance of strict regulations, effective supervision by the Manpower Office, and the need for policy reformulation so that the rights and positions of internship participants are truly protected by law.